A new self-adjustable glaucoma valve - Rafiei, Soroush; Gerber, Julien Maxime; Bigler, Stéphane; Stergiopulos, Nikolaos (Frontiers in Bioengineering and Biotechnology, 2024)
Glaucoma, the leading cause of irreversible blindness globally, affects more than 70 million people across the world. When initial treatments prove ineffective, especially for cases with high intraocular pressure (IOP), the preferred approach involves employing glaucoma drainage devices (GDDs). This study introduces a novel self-adjustable glaucoma drainage device (SAGDD) designed to maintain IOP within the desired biological range (10 mmHg < IOP < 18 mmHg) by dynamically modulating its fluidic resistance. Inspired by the starling resistor, we designed a circular valve with a thin, flexible membrane placed over the valve's inlet and outlet. To achieve the ideal design for the SAGDD and optimize its parameters, we utilized fluid-solid interaction (FSI) numerical models and conducted parametric studies, wherein simulations demonstrated the validity of the concept. Subsequently, to confirm and validate the numerical results, we fabricated a SAGDD at a 3:1 scale and subjected it to in vitro testing. Our findings demonstrate that, on a 3:1 scale, a circular SAGDD with a diameter of 8.1 mm and a stainlesssteel membrane with a thickness of 10 µm effectively maintained IOP within the target range when the membrane exposed to external pressures of 7.5 or 10 mmHg. In summary, our study establishes a strong foundation for further exploration of the potential efficacy of SAGDD as a promising treatment for glaucoma. The cost-effectiveness and simplicity of its design, devoid of costly instrumentation, hold considerable promise in addressing the challenges associated with glaucoma.